2011
DOI: 10.1371/journal.pone.0017002
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Tibetans and Their Genetic Basis in Adapting High-Altitude Environments

Abstract: Since their arrival in the Tibetan Plateau during the Neolithic Age, Tibetans have been well-adapted to extreme environmental conditions and possess genetic variation that reflect their living environment and migratory history. To investigate the origin of Tibetans and the genetic basis of adaptation in a rigorous environment, we genotyped 30 Tibetan individuals with more than one million SNP markers. Our findings suggested that Tibetans, together with the Yi people, were descendants of Tibeto-Burmans who dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 46 publications
3
142
0
Order By: Relevance
“…However, genetic adaptation can result from selection at more than one loci, and multiple studies indicate that Tibetan genetic selection has occurred not only at the PHD2 locus, but also at the HIF2A locus (3,(5)(6)(7)(8)(9). Importantly, two of these studies (3,5) demonstrated both a strong association between the Tibetan HIF2A haplotype and low hemoglobin concentration (which is controlled by the HIF-2␣ target gene, EPO (37)(38)(39)(40)), thereby providing compelling evidence that the HIF2A allele is a loss of function allele.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic adaptation can result from selection at more than one loci, and multiple studies indicate that Tibetan genetic selection has occurred not only at the PHD2 locus, but also at the HIF2A locus (3,(5)(6)(7)(8)(9). Importantly, two of these studies (3,5) demonstrated both a strong association between the Tibetan HIF2A haplotype and low hemoglobin concentration (which is controlled by the HIF-2␣ target gene, EPO (37)(38)(39)(40)), thereby providing compelling evidence that the HIF2A allele is a loss of function allele.…”
Section: Discussionmentioning
confidence: 99%
“…2 This disease is also observed in the highlands in immigrants who lived at sea level and were subsequently exposed to HA for several years. 27 This disease mainly occurs in populations with short-term residence at HA, as in some Andean 28 and most Han 29 and North American 30 inhabitants, whereas it is less common in Tibetans, 31 the group with the longest residence time in highland places. Hypoventilation, particularly during sleep, appears to be the dominant cause of hypoxaemia in patients with CMS.…”
Section: Chronic Hypoxaemia and Chronic Mountain Sickness (Cms)mentioning
confidence: 99%
“…Third, we overlapped the "WA" dataset with genotype data for the Sherpa and Tibetans genotyped on Illumina arrays. Specifically, we took 21 Sherpa individuals described as the "high-altitude proxy" samples in a previous study (Jeong et al 2014) and 30 Tibetans from near Lhasa, Tibet Autonomous Region in China (Wang et al 2011). We used the overlapping 45,513 SNPs ("WHA" dataset, for worldwide, high-altitude and Ainu data) for most of the analyses along with the WA dataset to investigate the genetic relationships of the Ainu and the high-altitude East Asians.…”
mentioning
confidence: 99%